The Anxiety in Primigravida about Adaptation to Physiological Changes During Pregnancy - Erma Herdyana; Betristasia Puspitasari (JURNAL KEBIDANAN, 2021)
Pregnancy causes major changes in the mother's body that is less understandable to be considered mysterious and anxiety. Changes in the body of pregnant women Primigravida occur as a result of an imbalance of the hormones progesterone and estrogen. Necessary adaptation to reduce the anxiety of the changes that occur during pregnancy to maintain physical and mental health. Scientists found more than half (54%) mothers have a sense of anxious and more than a third (37%) showed signs of depression at a certain period in the period of pregnancy. This research uses Descriptive with Cross Sectional approach. This study was conducted in January 2020. Population and Sample in this study were 22 respondents Primigravida in BPM Ny. Ani., sub District Baron, District of Nganjuk. Data analysis using quantitative approach. The results of the research show the characteristics of gestational age from 13 to 28 weeks as many as 13 respondents (59%) and the characteristics of the gestational age 29-40 weeks as much as 9 respondents (41%). After analysis with a quantitative approach using the percentage obtained results of the 22 respondents (100%) primigravida with mild anxiety